Discriminating early-stage diabetic retinopathy with subjective and objective perimetry - Sabeti, Faran; van Kleef, Joshua P.; Iyer, Rakesh M.; Carle, Corinne F.; Nolan, Christopher J.; Chia, Rong Hui; Maddess, Ted (Frontiers in Endocrinology, 2024)
To prevent progression of early-stage diabetic retinopathy, we need functional tests that can distinguish multiple levels of neural damage before classical vasculopathy.To that end we compared multifocal pupillographic objective perimetry (mfPOP), and two types of subjective automated perimetry (SAP), in persons with type 2 diabetes (PwT2D) with either no retinopathy (noDR) or mild-to-moderate non-proliferative retinopathy (mmDR). Both eyes were assessed by two mfPOP test methods that present stimuli within either the central ±15° (OFA15) or ±30° (OFA30), each producing per-region sensitivities and response delays. The SAP tests were 24-2 Short Wavelength Automated Perimetry and 24-2 Matrix perimetry. Five of eight mfPOP global indices were significantly different between noDR and mmDR eyes, but none of the equivalent measures differed for SAP. Per-region mfPOP identified significant hypersensitivity and longer delays in the peripheral visual field, verifying earlier findings. Diagnostic power for discrimination of noDR vs. mmDR, and normal controls vs. PwT2D, was much higher for mfPOP than SAP. The mfPOP per-region delays provided the best discrimination. The presence of localized rather than global changes in delay ruled out iris neuropathy as a major factor. mfPOP response delays may provide new surrogate endpoints for studies of interventions for early-stage diabetic eye damage.